FRI0515 Neutrophil-Specific S100A12 Phenotype Correlates to Genotype in Familial Mediterranean Fever. (9th June 2015) - Gohar, F.; Orak, B.; Jeske, M.; Lieber, M.; von Bernuth, H.; Giese, A.; Weissbarth-Riedel, E.; Haas, P.; Dressler, F.; Holzinger, D.; Lohse, P.; Neudorf, U.; et al.
Abstract : Background: Familial Mediterranean Fever (FMF) is an autoinflammatory disorder associated with MEFV pyrin-encoding gene mutations. S100A12 is a pro-inflammatory "damage associated molecular pattern" molecule and is strongly elevated in active FMF Objectives: To investigate the association between genotype and S100A12 secretion in clinically active, inactive and subclinical disease in vitro and ex vivo . Methods: Serum S100A12 concentration was retrospectively analysed for 125 patients in the German Auto-Inflammatory Diseases Network (AID-Net) Registry according to disease activity and genotype. In vitro, secretion of S100A12, IL-18, IL-1beta and caspase-1 was measured after stimulation of neutrophils from six M694V -positive patients and four healthy controls (HC). Results: S100A12 hypersecretion correlated significantly with clinical disease activity and also with genotype in a "gene-dosing" way, being highest in homozygotes > compound heterozygotes > heterozygotes. M694V -positive heterozygous, compound heterozygous or homozygous patients h had higher S100A12 concentration during inactive and subclinical disease than M694V- negative heterozygous, compound heterozygous or homozygous patients respectively. In vitro, unstimulated neutrophils from M694V -positive patient spontaneously secreted higher S100A12, IL-8 and caspase-1 compared to healthy controls. Colchicine significantly inhibited secretion of S100A12 from stimulated and unstimulated patient neutrophils. Conclusions: FMF phenotype is known to be more severe in patients with M694V mutations. We describe for the first time a biomarker that correlates with clinical disease activity and FMF genotype both ex vivo and in vitro, which has implications for clinical management. References: Wittkowski H. et al. Pediatr Rheumatol 2008. Kallinich T. et al. ARD 2010. Jeske M et al. Klin Pädiatrie 2013. Disclosure of Interest: None declared